EFEKTIVITAS AIR ABRASION TERHADAP KEBOCORAN MIKRO RESIN KOMPOSIT FLOWABLE DAN RM-GIC LESI SERVIKAL NON KARIES - Jessica Budiono; Ade Prijanti Dwisaptarini; Melaniwati Melaniwati (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2023)
Introduction: Based on the etiology, the cervical lesion is divided into carious and non-carious lesions. Cervical cavity fillings frequently experience failures, which lead to microleakage. Flowable composite resins and RM-GIC are frequently used as restorative materials for cervical cavities. The application of an air abrasion technique before restoration can increase the bond between the restorative material and the tooth structure. Purpose: To determine the effect of the air abrasion technique on the micro-leakage of non-carious cervical lesions with flowable composite resin and RM-GIC. Method: A total of 28 premolar samples were prepared for the cervical cavity. The samples were randomly divided into 4 groups (n = 7). Group I: air abrasion technique (AquacareTM Twin, Velopex International, London, UK) with flowable composite resin restoration (Filtek, 3M USA), Group II: air abrasion technique with RM-GIC restoration (Fuji II LC, Japan), Group III: flowable composite resin restoration without air abrasion technique, Group IV: RM-GIC restoration without air abrasion technique. Microleakage was assessed using the dye penetration method and observed using a stereomicroscope (ZEISS Stemi 305, German) with a magnification of 20x. The research data were analyzed using the Kruskal-Wallis test and Mann-Whitney test. Results: The flowable composite resin restoration group with the air abrasion technique had the lowest microleakage (p<0,05) than other restoration groups. There was no significant difference between the RM-GIC restoration group with air abrasion technique and the RM-GIC     group      without      air      abrasion      technique (p≥0.05). Conclusion: Applying the air abrasion technique before restoration with flowable composite resin restorative material resulted in the lowest microleakage.